Work Ethics, Wage Systems, and Bonuses: Examining Construction Worker Performance in Developing Economies - Nafisah, Zahrotun; Ubaid, Ubaidullah Muayyad; Lailatul Hasanah (Asian Journal of Law and Islamic Finance, 2025)
The construction sector remains a critical employment source in developing economies, yet understanding the determinants of worker performance in this informal labor market remains limited. This study addresses the gap by examining how work ethics, wage systems, and bonus provisions simultaneously influence construction worker performance in rural Indonesia. Using a quantitative approach with saturated sampling, we surveyed 97 construction workers in Gapurana Village, Talango District, Sumenep Regency. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression in IBM SPSS 23. Results reveal that work ethics (t = 2.892, p = 0.005), wage systems (t = 3.439, p = 0.001), and bonus provisions (t = 2.006, p = 0.048) each significantly and positively influence worker performance. The simultaneous effect of all three variables was highly significant (F = 33.965, p < 0.001), explaining substantial variance in performance outcomes. These findings demonstrate that performance enhancement in informal construction sectors requires multidimensional interventions beyond mere financial compensation. The study contributes to Islamic economics literature by providing empirical evidence on labor justice and welfare enhancement mechanisms. For policymakers and contractors, results suggest that integrating ethical development programs with fair wage systems and performance-based incentives creates synergistic effects on worker productivity, aligning with Islamic principles of just compensation and human dignity in employment relationships. Keywords: work ethics, wage systems, bonuses, construction worker performance